From justification to evaluation: Building information modeling for asset owners - Love, Peter; Simpson, Ian; Hill, Andrew; Standing, Craig (Elsevier BV, 2013)
Building information modeling (BIM) is an emerging technology focused methodology that can be used to improve the performance and productivity of an asset's design, construction, operation and maintenance process. Typically the investment justification process for BIM has been based upon the utilization of the return on investment (ROI). This measure does not accurately reflect the 'real' costs and benefits that are associated with implementing BIM by an asset owner. With this in mind, a benefits evaluation framework that looks beyond ROI and takes into account the evolving nature of BIM by incorporating intangible benefits and indirect costs is presented and discussed. To acquire the wide range of benefits that BIM can offer asset owners, it is proffered that they should shift their mindsets away from justification using ROI to a process of evaluation that encompasses the appraisal of value and benefits' realization.